2021
DOI: 10.3390/ma14195487
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hydrated Lime and Cellulose Ether Admixture on Water Retention, Rheology and Application Properties of Cement Plastering Mortars

Abstract: In this article, the effect of hydrated lime and cellulose ether on the water retention, rheology, and application properties of plasters was studied. For mortars, the consistency, bulk density, and water retention were tested. Rheological measurements of pastes included yield stress and plastic viscosity. In addition to standard tests of mortars and examining the rheological properties of the pastes, a proprietary method for testing the application properties was proposed. The obtained research results made i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The production of these admixtures includes various steps like grinding, activation with NaOH aqueous solution, a heterogeneous reaction with an etherifying agent, neutralization, isolation of crude cellulose ether, puri cation, drying, and packaging (Strunk, 2012). These cellulose derivatives play a role in controlling water retention in fresh-state mortars, enhancing adhesion power (Spychał & Dachowski, 2021) (Patural et al, 2011), and in uencing rheological properties like viscosity and yield stress. Their primary purpose is to improve mortar workability (Cappellari, The use of either Polyvinyl Alcohol or cellulose ether for mortar fresh/hardened-state properties enhancement has garnered signi cant attention among researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The production of these admixtures includes various steps like grinding, activation with NaOH aqueous solution, a heterogeneous reaction with an etherifying agent, neutralization, isolation of crude cellulose ether, puri cation, drying, and packaging (Strunk, 2012). These cellulose derivatives play a role in controlling water retention in fresh-state mortars, enhancing adhesion power (Spychał & Dachowski, 2021) (Patural et al, 2011), and in uencing rheological properties like viscosity and yield stress. Their primary purpose is to improve mortar workability (Cappellari, The use of either Polyvinyl Alcohol or cellulose ether for mortar fresh/hardened-state properties enhancement has garnered signi cant attention among researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Admixtures are supplied as powders, the typically used low dosages being 0.3–1.5% of the weight of the cement. The researchers have established [ 11 , 12 , 13 , 14 ] that the introduction of additives improves workability and lowers the water demand of the mix, confers air entrainment, or adds waterproofing qualities. These changes have the potential to decrease cracking through improvements in the paste–aggregate bond and to increase the strength of hardened mortars.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the study [ 13 ], a material with beneficial technical and technological properties that are relevant for mortars administered by machine can be obtained due to the rheology of plastering mortars with hydrated lime and cellulose ether. The authors of [ 32 ] have shown that the presence of cellulose ethers in hydraulic lime-based mortars may decrease the density of mortars in a plastic state and improve their frost resistance due to higher open porosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of rheology several approaches are known. Mineral admixtures such as clays and lime are used, or cellulose derivatives can be added [2][3][4][5]. A lightweight filler or aggregate (i. e. perlite, vermiculite etc.)…”
Section: Introductionmentioning
confidence: 99%